The Effect of Emotional Intelligence on Work Outcomes in the Construction Industry - Perera, Manjula (Auckland University of Technology, 2021)
This report identified and reviewed published material on emotional intelligence (EI) and its effect on work outcomes in the construction industry. The primary objective of this systematic literature search and critical review study was to synthesise the research on work outcomes of emotional intelligence (EI) in the construction industry to develop broad and robust conclusions on the state of knowledge. The second objective was to establish what is uncertain, unknown, and controversial and formulate recommendations for future research. The research is necessary because it allows for a bridging of the gap between research and practice. This systematic literature search and critical review focuses on 16 critical peer-reviewed articles that investigated the relationship between EI and work outcomes. The research findings show that EI is significantly correlated with job commitment, job performance, and job satisfaction. The study concludes by discussing the limitations of the literature in EI and recommendations for future research.
Keywords: Emotional Intelligence; Work Outcomes; Job Commitment; Job Performance; Job Satisfaction; Construction Industry